Accentuated eccentric resistance training: Effects on physical performance in male and female athletes - Galiano, C.; Floria, P.; Muñoz-López, A.; Sáez de Villarreal, E.; Nuñez, F. J. (Journal of Sports Sciences, 2024)
This study aimed to compare the effects of an accentuated eccentric training programme on physical performance between men and women. Distributed in two groups by gender, 21 male and 21 female athletes performed four sets of seven repetitions of the half-squat exercise twice per week for 6 weeks. Both groups lifted the same absolute load using a rotary inertial device. To accentuate the eccentric action, the eccentric load was twice as heavy as the concentric load. Vertical jump, sprint, and change of direction (COD) performances were measured pre- and post-intervention. To measure strength gains, vertical ground reaction forces were measured for each repetition of the entire training programme. Vertical jump improved post-intervention (MG: 33.88 ± 4.94 to 35.41 ± 4.86; FG: 20.60 ± 4.62 to 22.12 ± 4.32; p < 0.001; Eta2p = 0.42), while sprint (MG: 3.08 ± 0.11 to 3.07 ± 0.13; FG: 3.66 ± 0.23 to 3.64 ± 0.23) and COD (MG: 7.77 ± 0.42 to 7.61 ± 0.47; FG: 8.44 ± 0.58 to 8.38 ± 0.57) remained unchanged. Concentric and eccentric forces increased for both groups from session 1 to 4 (p < 0.001; Eta2p >0.39), while only peak eccentric forces increased until session 12 (p = 0.009; Eta2p = 0.21). In conclusion, even when men are able to produce greater forces with similar loads, accentuated eccentric RT produces similar strength and strength-related adaptations in male and female athletes.